PENINGKATAN KETERAMPILAN DIGITAL UMKM MELALUI PROGRAM SOCIAL MEDIA SELLER (SMS) - Ade Mutiara Putri Nasiub; Renilda Ariyani Saragih; Novi Nanda Arifa; Mirna Puspita; Jistian Arnal Dia Tamonob; Frans Frans; Erlianda Saputra; Elsa Hesty Mirani; Cahaya Dinata; Putri Rasti Ramadhani (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
The Social Media Seller (SMS) program is a community service activity that aims to improve the skills of Micro, Small, and Medium Enterprises (MSMEs) in utilizing social media as a means of product promotion. This activity was carried out in the area of Jl. Pala Raya and Jl. Merica, Pondok Cabe Udik, Pamulang, South Tangerang, through four main stages: observation, preparation, implementation, and evaluation. There were three meetings during the implementation of the activity, which included socialization, pretest, content creation training, field practice, editing, content uploading, and posttest. The results of the posttest showed a significant improvement in the participants' understanding and skills in creating and promoting product content digitally. Internal evaluation by the implementation team shows that the activities are running as planned and have a positive impact on the empowerment of MSMEs in the digital era.